Impact of the Implementation of Resources with Augmented Reality in Education - Cóndor-Herrera, Omar (2022)
Augmented reality (AR) has shown positive effects in education. In the present investigation, the results of an educational intervention, which consisted in the implementation of AR resources in the teaching process, are presented. The research had as objectives A) to analyze students’ perspectives on the implementation of AR in the educational field; B) to design resources with AR with the participants, as products of their projects; and C) to compare the performance of students doing projects with AR with their performance in a project done previously. The study was carried out with a population of 39 students between 12 and 16 years old who developed research projects on various topics in which they had to develop a product as the result of their research. The duration of the project was 6 weeks, for which the students worked in groups with the PBL methodology. To collect information about the learning experience, a survey was applied to the participants at the end of the intervention. Products, because of the project, were developed and presented by the students, and the grades obtained in the development of the project and qualifications obtained in previous projects were compared. Once the results were analyzed, it was evident that A) the vast majority of students surveyed gave answers in favor of the use of the technology to improve their motivation to learn, which significantly improved their willingness to carry out learning activities; B) the products developed were brochures and posters assembled with AR resources; and C) an increase of 2.24 points in the course average occurred in relation to the previous project.